Implementasi Growing Garden pada Perancangan Sekolah dan Tempat Terapi Khusus Anak Autisme di Surabaya - Stefanie Sukma Adhitama (Intra, 2016)
The Interior Design of School and Special Children Autism Therapy in Surabaya is designed due to the increasing number of children who suffer from autism in Indonesia especially Surabaya. However, these kind of facilities are still inadequate in Surabaya, which makes many children with autism didn’t receive any early treatment. The existence of this design is expected to embody and provide an adequate facilities for treatment and education activities. In addition, this facility is also made for parents whose children suffered from autism and public to get the correct information about how to handle children with autism. As an appreciation for the students, this facility also provides a place to appreciate the work of their students. According to Bryan Lawson there are four stages of the design’s method, which are assimilation, general study, development, and communication. The concept of growing garden has chosen because it has the meaning of growing, which the growth that the writer expected is the growth to be better. The Growth which has chosenconsists three areas of education i.e. intelligence, creativity, and life skill.Garden has chosen as the theme of design because meaning that this facility can accommodate all activities both learning and therapy. Besides, therapy facilities is suggested to use the natural approach so that the process of restoring will be fasten. The implementation of the concept of generated through the management of the zoning and circulation, form, color and also the management of furniture. So, this design can provide comprehensive facilities namely providing school facilities covering pre-school and primary schools, therapy facilities covering sensory integration therapy space, soft-play, occupation, speaking, technique, hygiene and toilet, health care, and self-development. As a place to give information for parents and public, this facility provides a meeting room and a hall facility to hold seminar. Hall also can be used for students to hold a festival, and there is mini gallery that is used to exhibit student’s works to people who come to this facility as a form of appreciation for the students’s works.